(Un)related variety and employment growth at the sub‐regional level*. (6th January 2017) - Firgo, Matthias; Mayerhofer, Peter
Abstract: Empirical results on the link between growth and diversity in (un)related industries proved to be highly dependent on the specific regional, temporal and econometric context. Using highly disaggregated employment data at the sub‐regional level, we find that higher employment growth in Austria is mainly linked to unrelated variety. However, in‐depth analyses by sectors and regional regimes illustrate substantial heterogeneity in the results, with services and a large number of relatively small non‐urban regions driving the overall results. Thus, our findings argue against structural policy conclusions based on assessments neglecting the specific sectoral and regional context.